Pancreatic Schwannoma: A Case Report and Literature Review with Special Reference to Imaging Features - Suzuki, Shiji; Kaji, Satoshi; Koike, Nobusada; Harada, Nobuhiko; Hayashi, Tsuneo; Suzuki, Mamoru; Hanyu, Fujio; Ban, Shinichi (JOP. Journal of the Pancreas, 2016)
Context We report the imaging features of pancreatic schwannomas, a rare benign type of pancreatic tumor. Case report A 66-year-old woman was admitted to our hospital with a pancreatic tumor indicated in medical examinations. Computed tomography (CT), magnetic resonance imaging (MRI) and endoscopic ultrasonography (EUS) revealed a solid and cystic tumor, 3 cm in diameter, within the body of the pancreas. Contrast-enhanced CT, MRI and ultrasonography showed partial enhancement in the solid component. Endoscopic retrograde cholangiopancreatography (ERCP) and angiography showed no abnormal findings. A distal pancreatectomy together with a splenectomy and lymph node dissection were performed with a tentative diagnosis of mucinous cystic neoplasm of the pancreas. The cut surface of the resected pancreas showed a well-demarcated, pale yellow, solid tumor within the pancreas parenchyma. Histopathological examination of the tumor revealed proliferation of the spindle cells showing interlacing and palisading patterns. Immunohistochemically, these spindle cells were positive for S-100 protein and vimentin, and negative for alpha-smooth muscle actin, CD34, and cytokeratin. Thus the tumor was diagnosed as a pancreatic schwannoma. Conclusion CT and US can detect pancreatic schwannomas as solid and cystic masses, and MRI shows a relatively characteristic feature. Imaging procedures such as CT, MRI and US are able to differentiate a pancreatic tumor, such as a pancreatic schwannoma. Image: Contrast-enhanced US shows partial enhancement at the solid component.